2002
DOI: 10.1152/ajpregu.00051.2002
|View full text |Cite
|
Sign up to set email alerts
|

Arterial baroreflex function and cardiovascular variability: interactions and implications

Abstract: The arterial baroreflex contributes importantly to the short-term regulation of blood pressure and cardiovascular variability. A number of factors (including reflex, humoral, behavioral, and environmental) may influence gain and effectiveness of the baroreflex, as well as cardiovascular variability. Many central neural structures are also involved in the regulation of the cardiovascular system and contribute to the integrity of the baroreflex. Consequently, brain injuries or ischemia may induce baroreflex impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(206 citation statements)
references
References 120 publications
(139 reference statements)
12
183
0
7
Order By: Relevance
“…Recent evidence suggests that changes in arterial baroreflex control and the autonomous nervous system are involved in the development and maintenance of hypertension. [29][30][31] In a classic study carried out in the 1960's, Bristow et al 32 reported for the first time that the baroreflex control of HR in patients with hypertension was significantly lower than that of normotensive individuals. Herein, we have observed that baroreflex sensitivity in normotensive rats is much higher than in SHRs, which supports the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that changes in arterial baroreflex control and the autonomous nervous system are involved in the development and maintenance of hypertension. [29][30][31] In a classic study carried out in the 1960's, Bristow et al 32 reported for the first time that the baroreflex control of HR in patients with hypertension was significantly lower than that of normotensive individuals. Herein, we have observed that baroreflex sensitivity in normotensive rats is much higher than in SHRs, which supports the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Because cardiovascular events most frequently occur in the morning hours (17)(18)(19)(20), BP elevation and the occurrence of cardiovascular events in the morning would have the same pathological background. Impaired BRS is associated with enhanced BP variability (21,22) and poor BP control in hypertensive patients (23). The reason why BRS was independently associated only with morning BP is unknown, but one possible explanation is that activation of the sympathetic nervous system, which is seen in hypertensive patients with morning hypertension, decreases BRS (24,25).…”
Section: Arterial Brs and Bp Controlmentioning
confidence: 99%
“…BP variability, and more specifically LF SBP , is influenced by a multitude of physiological factors (17), which in the short-term include excitatory vasoconstrictive neural mechanisms, modulatory effects of baroreflex, and local effects of the nitric oxide system (16,24,27,34). However, despite this composite origin, LF SBP is commonly considered a marker of overall sympathetic influence to the vascular system (23).…”
Section: Cardiovascular Variability and Amsmentioning
confidence: 99%